Pengaruh Personal dan Lingkungan Fisik Terhadap Kepuasan Pelanggan Café Waroeng Steak and Shake 3 - Muhammad Ihsan Naufal (Fakultas Ekonomi dan Bisnis Universitas Pasundan, 2021)
This study aims to examine the effect of personal and physical environment resources on customer satisfaction in Waroeng Steak and Shake Bandung, both simultaneously and partially. This research uses descriptive and verification research methods. This research takes place in Waroeng Steak and Shake Bandung, where the number of café visitors is smaller than the number of other café visitors. The number of complaints of café visitors during 2018 was 109 complaints. From the results of this study, it can be concluded that the magnitude of the simultaneous influence of personal and the physical environment on customer satisfaction is 52.4%. The magnitude of the effect of partial personal on customer satisfaction by 17%, while the effect of partial physical environment on customer satisfaction by 38%.